Art Forum Berlin 1999 : Katalog - art forum Berlin 1999; Kaernbach, Andreas; Krüger, Thomas; Stempel, Karin; Weiss, Evelyn; Werner, Klaus (Berlin : Projektgesellschaft, 1999)
Isaacs, John ; Rosanov, Michail ; Canogar, Daniel ; Rasmussen, Steen Moller ; Matelli, Tony ; Hirschhorn, Thomas ; Hilgemann, Ewerdt ; Séguin, Marc ; Troger, Gustav ; Schuster, Michael ; François, Michel ; Frandsen, Erik A. ; Xu Bing ; Outerbridge, Paul ; Prangenberg, Norbert ; Billgren, Ernst ; Weirich, Susanne ; Kelly, Mary ; O'Brien, Abigail ; Ritchie, Matthew ; Neto, Ernesto ; Frieling, Gijs ; Appelt, Siegrun ; Rosenblum, Adi ; Muntean, Markus ; Fleury, Sylvie ; Huber, Thomas ; Fairhurst, Angus ; Praschak, Erich ; Martin, Ron ; Ballester, José Manuel ; Gravinese, Diego ; Völker, Cornelius ; Jenssen, Olav Christopher ; Weiner, Lawrence ; Goedicke, Claus ; Amondarain, Jose Ramon ; Rauch, Neo ; Hays, Dan ; Peljhan, Marko ; Mengyan, Andras ; Förg, Gunther ; Nöger, Udo ; Pernice, Manfred ; LeWitt, Sol ; Meyer, Nanne ; Armstrong, David ; Huber, Stephan ; Koberling, Bernd ; Kippenberger, Martin ; Harrison, Rachel ; Martinez Celaya, Enrique ; Günther, Beate ; Kern, Stefan ; Damisch, Gunter ; Dzama, Marcel ; Almond, Darren ; Meigs, Sandra ; Hamak, Herbert ; Belag, Andrea ; Armstrong, L.C. ; Bevan, Tony ; Langlands & Bell ; Kappos, Marina ; Kaligofsky, Werner ; Rayson, David ; Vitali, Massimo ; Spaans, Jean-Marc ; Furunes, Anne Karin ; Burton, Jeff ; Appelt, Dieter ; Koppitz, Rudolf ; Müller, Claudia & Julia ; Altenburger, Stefan ; Tandberg, Vibeke ; Grauer, Phil ; Deutsch, David ; Neuwirth, Flora ; Schimansky, Hanns ; Dimitriadin, Christina ; Voshiko, Seino ; Root, Ruth ; Walde, Martin ; Sanguineti, Pietro ; Renner, Lois ; Schiess, Adrian ; Hofer, Siggi ; Moffatt, Tracey ; Kuitenbrouwer, Mirjam ; Cahn, Miriam ; Nicolson, Seamus ; McCaslin, Matthew ; Friberg, Maria ; Lind, Karin ; Fleury, Sylvie ; Zaugg, Rémy ; Wodiczko, Krzysztof ; Belag, Andrea ; etc.
art forum Berlin 1999, 30 sept to 4 oct 1999
Duits & Engels
boek